11.9k views
1 vote
Solve: 2x-3= 5(x+ 6)
OA. x= -9
OB. x=-11
OC. x=-3
OD. x- 33

User BenCamps
by
4.8k points

2 Answers

5 votes

Answer:

x = -11

Explanation:

2x-3 = 5x+30

2x = 5x+33

2x - 5x = 33

-3x = 33

33รท(-3)

x = -11

User Matt Kieran
by
5.0k points
3 votes

Answer: the correct answer is b x=11

Explanation:

2x - 3x + 3x = 5x + 30 + 3

2x = 5x + 33

( 2x - 5x = 5x + 33 - 5x

(1/3)-3x = 33x (1/3) Here we divide it but since it is 1/3, it is the same as dividing 3 divided by 11

1x = 11

x=11

User Rohan Pujari
by
6.2k points